2019
DOI: 10.1093/ejo/cjz055
|View full text |Cite
|
Sign up to set email alerts
|

Bimaxillary surgery to correct high-angle class II malocclusion: does a simultaneous genioplasty affect long-term stability?

Abstract: Summary Background and objectives High-angle skeletal Class II malocclusion is one of the most challenging dentofacial deviations to treat and, in adults, a combination of orthodontic treatment and bimaxillary orthognathic surgery is often indicated. This study examines the rate of clinically significant relapse and whether a genioplasty affects the treatment outcome of high-angle Class II malocclusions. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Nina el al. found that there was an open bite in half of the high-angle Class II patients who received bimaxillary surgery and mandibular skeletal relapse in 40% of the patients [ 26 ]. The adverse effect of anchorage loss tended to clockwise rotation of the occlusal plane and aggravate the treatment difficulty of high-angle Class II malocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Nina el al. found that there was an open bite in half of the high-angle Class II patients who received bimaxillary surgery and mandibular skeletal relapse in 40% of the patients [ 26 ]. The adverse effect of anchorage loss tended to clockwise rotation of the occlusal plane and aggravate the treatment difficulty of high-angle Class II malocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Nina el al. found that there was an open bite in half of the high-angle Class II patients who received bimaxillary surgery and mandibular skeletal relapse in 40% of the patients [21]. The adverse effect of anchorage loss would bring about clockwise rotation of the occlusal plane and aggravate the treatment di culty of high-angle Class II malocclusion.…”
Section: Discussionmentioning
confidence: 99%